Forecasting the yield of paddy at Chinsurah in West Bengal, using multiple regression technique - SHANKER, UPENDRA; GUPTA, BRD (MAUSAM, 1987)
Using the weather data as independent variables and yield data as dependent variable, multiple regression equation has been derived to forecast the yield of paddy at Chinsurah, a station in West Bengal, India. The data utilized is that of Coordinated Crop Weather Scheme. An estimate is also made of change in the final yield when the weather parameters change by five per cent from their normal value. The agreement between the estimated and actual yield is good. An yield forecast is also made using1969 and 1972 weather data with the help of derived regression equation. The agreement between actual and forecast yield is found to be good.